Comparison of methods for kinematic identification of footstrike and toe-off during overground and treadmill running - Fellin, R. E.; Rose, W. C.; Royer, T. D.; Davis, I. S. (Journal of Science and Medicine in Sport, 2010)
When analysing gait, the identification of the period of stance is often needed. Forceplates are typically used, but in their absence kinematic data can be employed. Five kinematic methods have been previously described in the literature. However, these methods have not been compared to each other for overground or treadmill running. Therefore, the purpose of this study was to compare these five kinematic methods of identifying the stance phase with vertical ground reaction force data both during overground and treadmill running. We recruited forty recreational runners (20 males) for this study. Twenty runners underwent an instrumented gait analysis during overground running, and twenty were tested during instrumented treadmill running. All runners ran at 3.35 m/s. Each kinematic method was compared with stance identified from the vertical ground reaction force (gold standard) for overground running. This method was then repeated for treadmill running. Two methods were found to be valid and reliable for determining footstrike. These were the time when the distal heel marker reached a minimum vertical position, and when the vertical velocity of this same marker changed from negative to positive. These methods had absolute errors that ranged from 22.4 ms to 24.6 ms for both modes of running. Toe-off was best identified using peak knee extension, with absolute errors of 4.9 ms for overground running and 5.2 ms for treadmill running. Utilising automated kinematic methods of determining stance will aid researchers studying running when forceplates are unavailable.